Violence against children and adolescents: reflective study on public policies - Quitéria Clarice Magalhães Carvalho; Maria Vera Lúcia Moreira Leitão Cardoso; Maria Josefina da Silva; Violante Augusta Batista Braga; Marli Teresinha Gimeniz Galvão (Rev Rene)
Violence takes up a prominent place in the modern society. It is considered a public health problem. The aim of this study was to describe policies related to violence against children and adolescents. It was a documentary and reflective study which involved data from 1982 to 2006. From the data, it was formulated the following category: public policies concerned violence against children and adolescents. It is inferred that the way they have been treated varies between negligence, punishment and mere measures of care. There are statutes, codes and laws; however it seems they need energetic effective measures to be put into effect. It is necessary to develop activities that propitiate possibilities of a life with respect to the children and adolescents. The phenomenon of violence must send the society to the tireless fight for the practice of democracy. Amongst the social elements, the nurse is detached for being present in many scenes of assistance to children and adolescents, having opportunity to contribute significantly to the detection, prevention and notification of such phenomenon.